Interior Rumah Huni Usaha Batik Sekar Kencana Lasem Jawa Tengah - Agustinus Michael Avilianto (Intra, 2016)
Lasem is a large port city of Majapahit Kingdom. The architectural style of Lasem City is a result of the combination between Southern China’s architectural styles, blends with Javanese’s architectural styles, and influenced by the Dutch’s, which developed over times. Lasem City also has Batik textile that represent the identity of the city. The Batik’s motif of Lasem City mostly called “Tiongkok Kecil (Small Chinese)”. Some local people are selling Batik as their livelihood. This research uses descriptive qualitative methods and aiming to describe about function, aesthetics, and interior’s atmosphere of Batik Lasem Home Business, which still preserves the Chinese’s culture. The Batik’s shop and the home living are separated. It portrays a different function of each room so that the Batik Lasem Home Business has a particular characteristic compared to another house.